Two new species of Phasmatocoris Breddin from Brazil, and description of the male of Phasmatocoris borgmeieri (Wygodzinsky) (Hemiptera: Heteroptera: Reduviidae: Emesinae) - Gil-Santana, Hélcio R. (Zootaxa, 2015)
Phasmatocoris catarinae sp. nov. and P. galvaoi sp. nov. (Hemiptera: Heteroptera: Reduviidae: Emesinae: Emesini) are described from Brazil based on female and male specimens. The male of Phasmatocoris borgmeieri (Wygodzinsky, 1945) is described and short taxonomical notes on this species and P. xavieri Gil-Santana et al., 2007 are provided.